2017
DOI: 10.1016/j.spa.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of the total number of critical points of random spherical harmonics

Abstract: Abstract. We determine the asymptotic law for the fluctuations of the total number of critical points of random Gaussian spherical harmonics in the high degree limit. Our results have implications on the sophistication degree of an appropriate percolation process for modelling nodal domains of eigenfunctions on generic compact surfaces or billiards.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 17 publications
(33 reference statements)
2
49
0
Order By: Relevance
“…s Note that also in this case, the second component is the leading term of the expansion and it is important to stress how the leading terms in the variances cancel in all cases at the threshold u = −∞; in other words, the variance is smaller when we focus on the total number of critical points (see Cammarota & Wigman, 2017). This is again a form of the so-called "Berry's cancellation phenomenon", which we have also discussed earlier for the Lipschitz-Killing curvatures.…”
Section: F I G U R Ementioning
confidence: 99%
See 3 more Smart Citations
“…s Note that also in this case, the second component is the leading term of the expansion and it is important to stress how the leading terms in the variances cancel in all cases at the threshold u = −∞; in other words, the variance is smaller when we focus on the total number of critical points (see Cammarota & Wigman, 2017). This is again a form of the so-called "Berry's cancellation phenomenon", which we have also discussed earlier for the Lipschitz-Killing curvatures.…”
Section: F I G U R Ementioning
confidence: 99%
“…Because this second‐order chaos component (and hence the leading term in the variance) vanishes at u=-,0, the next component becomes of interest; it can be shown that this term is proportional to the fourth‐order chaos, and indeed, for the total number of critical points, it holds that (see Cammarota & Wigman, ).Efalse[N-c(f)false]=2(+1)3+Ofalse(1false),Varfalse(N-c(f)false)=2log27π2+Ofalse(2false);moreover, it is also possible to consider separately extrema (minima and maxima) and saddles, yieldingEfalse[N-e(f)false]=(+1)3+Ofalse(1false),Varfalse(N-e(f)false)=2log4×27π2+Ofalse(2false),andEfalse[N-s(f)false]=(+1)3+Ofalse(1false),Varfalse(N<...>…”
Section: Characterization Of Critical Points For Random Spherical Harmentioning
confidence: 99%
See 2 more Smart Citations
“…This relates to the broad effort of understanding the statistical structure of stationary points (minima, maxima and saddles) of random landscapes which is of steady interest in theoretical physics [30][31][32][33][34][35][36][37][38][39], with recent applications to statistical physics [10,[34][35][36][38][39][40][41], neural networks and complex dynamics [42][43][44][45][46], string theory [47,48] and cosmology [49,50]. It is also of active current interest in pure and applied mathematics [51][52][53][54][55][56][57][58][59][60], For the model (1)- (2) in the simplest case d = 0 (x is a single point), the mean number of stationary points and of minima of the energy function was investigated in the limit of large N 1 in [35,38,39], see also [37,50,52]. It was found that a sharp transition occurs from a 'simple' landscape for µ > µ c (the same µ...…”
Section: Motivation and Goals Of The Papermentioning
confidence: 99%